'Two sides of the same coin'? A longitudinal analysis evaluating whether financial austerity accelerated NHS privatisation in England 2013-2020 - Anders Malthe Bach-Mortensen; Aaron Reeves; Benjamin Goodair (BMJ Publishing Group, 2024)
Objectives To understand the relationship between increasing privatisation of the NHS and austerity cuts to public funding.Design Longitudinal analysis.Setting 170 Clinical Commissioning Groups (CCGs) in England between 2013 and 2020.Intervention The UK austerity programme, spearheaded by the conservative-led governments of the 2010s, leveraged the 2008 financial crisis to roll-back spending to local government and social security spending. They also restricted the rate of growth in NHS spending-but cuts varied for different areas, often impacting deprived areas hardest.Main outcome For-profit outsourcing by NHS commissioners. After the implementation of the 2012 Health and Social Care act commissioners were encouraged and obliged to open contracts to the private sector. The uptake of for-profit outsourcing varied massively. Some CCGs contracted out almost half of their activity, and others almost none.Results We calculate the size of austerity across all CCGs. The financial restrictions meant that commissioners had, on average, £21.2 m more debt by 2021 than in 2014 in real terms. We find that there is a null and very small effect of changes to local NHS funding on for-profit outsourcing. A decrease in £100 per capita of NHS funding corresponds in a decrease in 0.441 percentage points (95% CI −0.240 to 1.121) of for-profit expenditure. We also find that local changes to public expenditure on the NHS, local government and social security do not confound the relationship between for-profit outsourcing and treatable mortality rates.Conclusions NHS privatisation at the local level does not appear to be a direct response to or result of austerity. That does not mean that it is unproblematic. Rather than being confounded by funding levels, the deteriorating health outcomes associated with privatisation should be considered as a distinct concern to the disastrous health effects of austerity policies.